Housing Wealth or Collateral: How Home Value Shocks Drive Home Equity Extraction and Spending - Søren Leth-Petersen; Henrik Yde Andersen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
We examine whether unanticipated changes in home values drive spending and mortgage-based equity extraction. To do this we use longitudinal survey data with subjective information about current and expected future home values to calculate unanticipated home value changes. We link this information at the individual level to high quality administrative records containing information about mortgage borrowing as well as savings in various financial instruments. We find that the marginal propensity to increase mortgage debt is 3-5% of unanticipated home value gains. We find no adjustment to other components of the portfolio, and we find that mortgage extraction leads to an increase in spending. The effect is driven by young households with high loan-to-value ratios which is consistent with the effect being driven by collateral constraints. Further, we find that the effect is driven by home owners who actively take out a new mortgage. The price effect is magnified among FRM borrowers who have an incentive to refinance their loans to lock in a lower market rate. These results point to the importance of the mortgage market in transforming price increases into spending and suggest that monetary policy can play an important role in transforming housing wealth gains into spending by affecting interest rates on mortgage loans.
Keywords: D12; D14; E21; E52; 330; Housing wealth effects; Mortgage market; House price expectations; Analysis of survey and administrative data